IMPLEMENTASI WEB SERVICE PADA SISTEM INFORMASI RUMAH SAKIT (Information Technology and Telematics, 2015)
Abstract A hospital information system should provide prompt and accurate information so that the information can be conveyed properly. Hospital information system provides a lot of convenience to the user to obtain information related to the hospital. However, hospital information system is available only to provide overall data. So it will be difficult for the user if they want to find out information data recap. The purpose of this research is to build a web service that can connect between the hospital information system with dashboard applications hospital. This system development method mrnggunakan prototype method, while designing the system using DFD (Data Flow Diagram) and flowchart. The software used in the development of the system, among others, MySQL, PHP, XAMPP and JSON as a data interchange format. The data contained in MySQL will be drawn through the combined query in a PHP file format. As for the output will produce JSON output format then the JSON data is displayed in a dashboard application. This study resulted in a web service system that can be used to display patient data recap contained in a hospital information system that will facilitate the patient data information contained in the hospital.   Keywords : web service, json, php, xampp